Il metodo di studio come «prima misura compensativa» per l'inclusione degli allievi con DSA: progetto per una ricerca esplorativa sulle scelte inclusive della scuola primaria e secondaria di primo grado - Lucia Chiappetta Cajola; Marianna Traversetti (LED Edizioni Universitarie, 2016)
The study describes framework, method and first results of an exploratory research conducted to examine how the italian school of full inclusion realizes education for all student, with specific attention to special educational needs. In detail, the research aims to describe the procedures used in primary and lower secondary school to facilitate the acquisition of a personal and flexible study method for students with learning difficulties and their classmates. In letterature, in fact, the study method is considered as the first balance measure for students with learning difficulties; consequently study method improvement is a very important school task. In addition, the school could ensure that the parents are able to support the development of children study method. According to this perspective, the study considers the environmental factors (WHO, 2007) of each school to highlight the interaction between the student individual condition and the context. The research examines four analisys dimensions related to the study method: cognitive and learning strategies, study planning and organization (use of materials, individuation of balance measures, timing, etc.), emotional management in study situations (learning motivation, students' acceptance of balance tools, teachers attitude, etc.) and inclusive pratices in school.